Physical Violence During Mandatory Psychiatric Treatment: Prevalence and Patient Characteristics - Verstegen, Nienke (Criminal justice and behavior, 2020)
This study explores variables that predict physical violence in 614 (forensic) psychiatric inpatients. All violent incidents that occurred in a Dutch forensic psychiatric hospital between 2014 and 2019 (N = 3,713) were coded with the Modified Overt Aggression Scale+ based on daily hospital reports and patients’ medical records. Binary logistic regression analyses examined which patient variables could differentiate between patients with and without physical violence during treatment and between patients with single and multiple incidents of physical violence. Variables included in the analyses were gender, legal status, borderline personality disorder, antisocial personality disorder, schizophrenia spectrum disorder, psychopathy (Psychopathy Checklist-Revised [PCL-R] score), self-harm during treatment, impulsivity, intellectual disability, and length of stay. A clear association was found between self-harm and inpatient physical violence on all outcome measures and in all analyses. Adequate monitoring of self-harm is advised as a strategy to early identify patients with a high risk to threaten ward safety.